One small step: A review of Plio‐Pleistocene hominin foot evolution. (21st December 2018) - DeSilva, Jeremy; McNutt, Ellison; Benoit, Julien; Zipfel, Bernhard
Abstract: Bipedalism is a hallmark of being human and the human foot is modified to reflect this unique form of locomotion. Leonardo da Vinci is credited with calling the human foot "a masterpiece of engineering and a work of art." However, a scientific approach to human origins has revealed that our feet are products of a long, evolutionary history in which a mobile, grasping organ has been converted into a propulsive structure adapted for the rigors of bipedal locomotion. Reconstructing the evolutionary history of foot anatomy benefits from a fossil record; yet, prior to 1960, the only hominin foot bones recovered were from Neandertals. Even into the 1990s, the human foot fossil record consisted mostly of fragmentary remains. However, in the last two decades, the human foot fossil record has quadrupled, and these new discoveries have fostered fresh new perspectives on how our feet evolved. In this review, we document anatomical differences between extant ape and human foot bones, and comprehensively examine the hominin foot fossil record. Additionally, we take a novel approach and conduct a cladistics analysis on foot fossils ( n = 19 taxa; n = 80 characters), and find strong evidence for mosaic evolution of the foot, and a variety of anatomically and functionally distinct foot forms as bipedal locomotion evolved.